Gene Dosage- and Age-Dependent Differential Transcriptomic Changes in the Prefrontal Cortex of Shank2-Mutant Mice - Lee, Seungjoon; Kang, Hyojin; Jung, Hwajin; Kim, Eunjoon; Lee, Eunee (Frontiers in Molecular Neuroscience, 2021)
Shank2 is an abundant postsynaptic scaffolding protein that is known to regulate excitatory synapse assembly and synaptic transmission and has been implicated in various neurodevelopmental disorders, including autism spectrum disorders (ASD). Previous studies on Shank2-mutant mice provided mechanistic insights into their autistic-like phenotypes, but it remains unclear how transcriptomic patterns are changed in brain regions of the mutant mice in age- and gene dosage-dependent manners. To this end, we performed RNA-Seq analyses of the transcripts from the prefrontal cortex of heterozygous and homozygous Shank2-mutant mice lacking exons 6 and 7 at juvenile (week 3) and adult (week 12) stages. Juvenile heterozygous Shank2-mutant mice showed upregulation of glutamate synapse-related genes, downregulation of ribosomal and mitochondrial genes, and transcriptomic changes that are opposite to those observed in ASD (anti-ASD) such as upregulation of ASD_down (downregulated in ASD), GABA neuron-related, and oligodendrocyte-related genes. Juvenile homozygous Shank2 mice showed upregulation of chromatin-related genes and transcriptomic changes that are in line with those occurring in ASD (pro-ASD) such as downregulation of ASD_down, GABA neuron-related, and oligodendrocyte-related genes. Adult heterozygous and homozygous Shank2-mutant mice both exhibited downregulation of ribosomal and mitochondrial genes and pro-ASD transcriptomic changes. Therefore, the gene dosage- and age-dependent effects of Shank2 deletions in mice include differential transcriptomic changes across distinct functional contexts, including synapses, chromatin, ribosomes, mitochondria, GABA neurons, and oligodendrocytes.